Осуществление юнгианской идеи русских как интуитивных интровертов в современной литературной фантастике - Radosz, Joanna (Studia Rossica Posnaniensia, 2022)
The paper aims at investigating the demonstration of Russian intuition in the contemporary Russian speculative fiction. The research thesis is that the Russians, both presented in literature and within the frames of the national character studies, manifest themselves as the intuitive introvert type according to Carl Gustav Jung’s classification. For validating the thesis, as far as the proposed literary works are concerned, one should use the instruments offered by cultural literary criticism along with the support of non-literary disciplines, such as intercultural communication and ethnopsychology. Moreover, one should consider also notes on Russian national character taken by Jung himself as well as studies on the sociocultural aspect of the analysed works. A wide range of methods and perspectives allows deep research of the “feeling – intuitive” Jungian scale as manifested within literary characters representing the Russian element (also called Russianness) in the selected works, which belong to the most significant and/or popular pieces of contemporary speculative fiction in Russia.